L1CAM Is a Marker for Enriching Corticospinal Motor Neurons in the Developing Brain - Samata, Bumpei; Takaichi, Rika; Ishii, Yuko; Fukushima, Kaori; Nakagawa, Harumi; Ono, Yuichi; Takahashi, Jun (Frontiers in Cellular Neuroscience, 2020)
The cerebral cortical tissue of murine embryo and pluripotent stem cell-derived neurons can survive in adult brain and extend axons to the spinal cord. These features suggest that cell transplantation can be a strategy to reconstruct the corticospinal tract (CST). It is unknown, however, which cell population makes for safe and effective donor cells. To address this issue, we grafted the cerebral cortex of E14.5 mouse to the brain of adult mouse and found that the cells in the graft extending axons along the CST expressed CTIP2. By using CTIP2:GFP knockin mouse embryonic stem cells, we identified L1CAM as a cell surface marker to enrich CTIP2+ cells. We sorted L1CAM+ cells from E14.5 mouse brain and confirmed that they extended a larger number of axons along the CST compared to L1CAM- cells. Our results suggest that sorting L1CAM+ cells from the embryonic cerebral cortex enriches subcortical projection neurons to reconstruct the CST.